Medición de la frecuencia frente a variaciones de carga utilizando un prototipo de generación - Cerna Pacheco, Marlon Alexander (2019)
This research work discloses the basics of power-frequency control in a synchronous generator in order to know the behavior of the frequency before load variations and operating parameters of the generation system in the real-time. It built a display module, monitoring in order to acquire frequency, speed and voltage data, using an Arduino Nano board and the Nextion screen through proper programming. This research studied the behavior of the voltage wave to determine the duration of each cycle using a reducer transformer and electrical circuit in order to convert the sine wave into a square wave allowing to obtain the duration of each cycle and through the crossings by zero to show the linear graph of the frequency measuring the duration time of the transients. For this procedure its was necessary to make a practice model due to frequency variations to understand the variables that are immersed in the P.F control. The experimental data show that by injecting a resistive load into the generating group of the Lab-Volt module the frequency decreases by 60% of its nominal value and stabilizes in a time of 10 seconds due to the increased load that directly affects the frequency. The results found in the investigation check that the voltage decreases between 30% and 40% due to a current flows in the generator winding which causes a voltage drop in the resistance.